2007
DOI: 10.1038/nmeth1036
|View full text |Cite
|
Sign up to set email alerts
|

Ultramicroscopy: three-dimensional visualization of neuronal networks in the whole mouse brain

Abstract: Visualizing entire neuronal networks for analysis in the intact brain has been impossible up to now. Techniques like computer tomography or magnetic resonance imaging (MRI) do not yield cellular resolution, and mechanical slicing procedures are insufficient to achieve high-resolution reconstructions in three dimensions. Here we present an approach that allows imaging of whole fixed mouse brains. We modified 'ultramicroscopy' by combining it with a special procedure to clear tissue. We show that this new techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1,028
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,113 publications
(1,033 citation statements)
references
References 16 publications
2
1,028
1
2
Order By: Relevance
“…In order to assess the pattern of growing axons, a three-dimensional analysis of the regenerating fibers was carried out in whole-mounted optic nerves after tissue clearing using a modified protocol previously described. 37,38 In the optic nerve segments situated between 100 and 300 mm past the lesion site, branched and unbranched axons could be distinguished, as well as axons that formed U-turns within this region (Figures 2e and f). We found that the proportion of branching axons did not significantly vary between Cnp-Cre þ / À xRtn4 flox/flox and Rtn4 flox/flox control mice (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the pattern of growing axons, a three-dimensional analysis of the regenerating fibers was carried out in whole-mounted optic nerves after tissue clearing using a modified protocol previously described. 37,38 In the optic nerve segments situated between 100 and 300 mm past the lesion site, branched and unbranched axons could be distinguished, as well as axons that formed U-turns within this region (Figures 2e and f). We found that the proportion of branching axons did not significantly vary between Cnp-Cre þ / À xRtn4 flox/flox and Rtn4 flox/flox control mice (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%
“…Light sheet microscopy or ultramicroscopy, originally developed in 1903 [41], reappeared in 1983 when it was applied to fixed and cleared tissue as orthogonal-plane fluorescence optical sectioning (OPFOS) [42], and as thin laser sheet imaging microscopy (TSLIM) in 2002 [43] finally being applied to whole fixed and cleared organs as ultramicroscopy [44]. However, it was not until Huisken et al in 2004 [45] presented selective plane illumination microscopy (SPIM) data applied to in vivo zebrafish imaging that light sheet microscopy really took off.…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…A recent neuroanatomical study, for example, succeeded in identifying and mapping 16 per cent of the approximately 100 000 neurons of the Drosophila brain [97], illustrating just how far we have progressed in the direction of understanding the circuitry of insects' brains. Other recent developments make the imaging of entire neural circuits, and possibly whole brains at micrometre resolution, increasingly feasible [98,99]. It is quite conceivable that as such technologies develop we will discover neural-computational solutions to cognitive tasks in non-human animals quite unlike those in humans (even where the behavioural outcomes might be similar).…”
Section: Data-driven Approaches To Behaviour and Cognitionmentioning
confidence: 99%